2022
DOI: 10.3389/fchem.2022.1052238
|View full text |Cite
|
Sign up to set email alerts
|

Caulerpa racemosa extract inhibits HeLa cancer cells migration by altering expression of epithelial-mesenchymal transition proteins

Abstract: Introduction: Cervical cancer is caused by persistent infections of human papillomavirus types 16 and 18. Also, it is classified as a malignancy since it is able to spread itself to other sites and form a metastasis. Lymph nodes metastasis is an important factor related to cervical cancer survival. The previous study reported that Caulerpa racemosa has an anti-cancer effect by inducing apoptosis by inhibiting p53 protein degradation in HeLa cancer cells. In this study, we conducted a follow-up test to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Research has demonstrated that the extract of C. racemosa , the green caviar, can inhibit the migration of HeLa cancer cells by altering the expression of proteins involved in epithelial–mesenchymal transition (EMT) [ 3 ]. Additionally, this extract has been shown to induce apoptosis in cancer cells by inhibiting the degradation of the p53 protein, a critical regulator of cell growth and apoptosis [ 3 ]. C. racemosa is rich in bioactive pigments such as chlorophyll and carotenoids, which are known for their antioxidant, anti-inflammatory, and anti-obesity properties [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has demonstrated that the extract of C. racemosa , the green caviar, can inhibit the migration of HeLa cancer cells by altering the expression of proteins involved in epithelial–mesenchymal transition (EMT) [ 3 ]. Additionally, this extract has been shown to induce apoptosis in cancer cells by inhibiting the degradation of the p53 protein, a critical regulator of cell growth and apoptosis [ 3 ]. C. racemosa is rich in bioactive pigments such as chlorophyll and carotenoids, which are known for their antioxidant, anti-inflammatory, and anti-obesity properties [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that the extract of C. racemosa, the green caviar, can inhibit the migration of HeLa cancer cells by altering the expression of proteins involved in epithelial-mesenchymal transition (EMT) [3]. Additionally, this extract has been shown to…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations